Sharia Governance and Regulatory Frameworks in Islamic Finance: A Systematic Qualitative Review of Institutional and Regulatory Perspectives - Isnaini Hani'ah (Journal of Halal Review, 2025)
Objective: This study aims to synthesize and interpret the conceptual development of Sharia governance and regulatory frameworks in Islamic finance through a systematic review of high-quality academic literature. This study seeks to identify conceptual patterns, regulatory dynamics, and implementation challenges that shape the evolution of Sharia governance in diverse jurisdictions. Research Design & Methods: This study uses a systematic qualitative literature review approach to scientific articles indexed in Scopus during the period 2009–2025. The selection process was carried out through stages of identification, screening, and inclusion based on criteria of thematic relevance, journal quality, and conceptual contribution. Data were analyzed using thematic synthesis to group findings into key conceptual themes related to the definition of Sharia governance, regulatory frameworks, and contemporary implementation dynamics. Findings: The results of the study show that Sharia governance does not have a single universal definition, but rather develops as a contextual and dynamic institutional concept. Early literature positioned it as a mechanism of normative compliance, while recent studies place it as a hybrid governance system involving interaction between Sharia authorities, state regulators, and international standards. The findings also reveal ongoing tensions between the independence of Sharia councils and the need for regulatory integration, as well as the increasing role of maqāṣid al-sharīʿa in expanding the orientation of Sharia governance from formal compliance to broader socio-economic objectives. Implications & Recommendations: Practically, this study recommends strengthening the design of co-regulation-based Sharia governance that can bridge normative legitimacy and regulatory stability. In terms of policy, harmonization of standards needs to be understood as an adaptive process, not a uniform formal convergence. Contribution & Value Added: This study provides a conceptual contribution by positioning Sharia governance as an integral part of modern institutional governance theory, as well as enriching the Islamic finance literature through a critical synthesis across disciplines and jurisdictions.